2008
DOI: 10.2214/ajr.07.2330
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Management of Complex Fibroadenomas

Abstract: Approximately 16% of fibroadenomas are complex. Complex fibroadenomas are smaller and appear at an older age. At a mean follow-up of 2 years, we found a low incidence of malignancy in complex fibroadenomas. Women with complex fibroadenomas may therefore be managed with a conservative approach, similar to the approach now recommended for women with simple fibroadenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 19 publications
5
98
1
Order By: Relevance
“…Juvenile fibroadenomas were the second most common histology seen in our cohort (5.9%), historically constituting 7% to 8% of all fibroadenoma subtypes [8,28,29]. Up to 10% to 25% of juvenile fibroadenomas can be multiple or bilateral, and most occur in adolescent African American adolescent girls [1,30].…”
Section: Discussionmentioning
confidence: 99%
“…Juvenile fibroadenomas were the second most common histology seen in our cohort (5.9%), historically constituting 7% to 8% of all fibroadenoma subtypes [8,28,29]. Up to 10% to 25% of juvenile fibroadenomas can be multiple or bilateral, and most occur in adolescent African American adolescent girls [1,30].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, histological diagnosis is typically unexpected (1,8,9,13,14). The mean age of patients with carcinoma in FA has been reported as 42-44 years, ~20 years subsequent to the peak age of occurrence of FA (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that complex fibroadenoma made up 0.6% (3) of cases and occurred in patients with average age of 24 years. In Israel, Sklair-Levy et al [19] reported that 15.7% of fibroadenoma were of the complex type.…”
Section: Characteristics Of Fibroadenoma In Nigerian Igbo Femalesmentioning
confidence: 99%